Solar photovoltaic soft stone plate and preparation method thereof

By introducing bonded photovoltaic decorative layer and base structure into soft stone slabs, combining amorphous silicon flexible solar thin film batteries and specific raw materials, the problem of single function of soft stone slabs is solved, efficient solar photovoltaic conversion and flexible performance is achieved, and the Market application.

CN119145588APending Publication Date: 2024-12-17WUXI TONGCHUANG COATING TECH ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411278231.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing soft stone slab has a single function and is only used as a wall finish material, lacks versatility, especially in terms of energy conversion.

Method used

Soft stone slabs composed of photovoltaic decorative layers and base layers bonded by adhesives. The photovoltaic decorative layers include amorphous silicon flexible solar thin film batteries. Through the use of functional auxiliary materials and polyurethane sealing adhesives, combined with raw materials such as acrylic emulsions, silicate cement, etc. The base layer is prepared and produced by rolling and laminating vacuum treatment technology.

Benefits of technology

It has achieved improvements in solar light conversion efficiency and flexibility of soft stone slabs, ensuring the expansion of product quality and market prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of soft stone plate production, in particular to a solar photovoltaic soft stone plate and a preparation method thereof. The soft stone plate is composed of a photovoltaic decoration layer and a base layer which are bonded through a binder, the photovoltaic decoration layer comprises a first film layer, an amorphous silicon flexible solar thin film cell and a second film layer, and the amorphous silicon flexible solar thin film cell is arranged between the first film layer and the second film layer. The first film layer is prepared by coating the surface of a PET film with functional auxiliary materials and then drying the PET film in a drying oven, and the base layer is prepared from acrylic emulsion, Portland cement, butylene diacrylate, sodium dodecyl benzene sulfonate, potassium sulfamate, reinforcing filler, water and the like as raw materials; the prepared soft stone plate with the solar photovoltaic function not only has good solar light conversion efficiency, but also has excellent flexibility, and the quality of the soft stone plate is effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft stone slab production, in particular to a soft stone slab with solar photovoltaic function and a preparation method thereof. Background Art

[0002] Soft stone slabs, also known as flexible decorative soft stone, are a new type of environmentally friendly wall decorative sheet material with a certain degree of flexibility. They are currently widely used in the market.

[0003] In the patent document with application number "CN202211120667.6" and titled "A lightweight soft stone board and its preparation method", it is recorded that "it includes a surface layer and a base layer from top to bottom, and the surface layer and the base layer are compounded and pressed together in a slurry state, and the thickness of the lightweight soft stone board is 6mm to 15mm. It also includes an intermediate layer, which is located between the surface layer and the base layer, and the intermediate layer and the surface layer and the base layer are compounded and pressed together in a slurry state. The lightweight soft stone board product of this application has the advantages of heat preservation, light weight and low cost. The application also discloses a method for preparing a lightweight soft stone board, including: preparing a surface layer slurry, preparing an intermediate layer slurry, preparing a base layer slurry, arranging the base layer slurry in a mold, covering the intermediate layer slurry on the upper surface of the base layer slurry to obtain a base-intermediate layer blank; covering the surface layer slurry on the upper surface of the intermediate layer to obtain a lightweight soft stone board blank; hot molding the blank to obtain a lightweight soft stone board. This method is easy to operate and can efficiently produce lightweight soft stone boards with stable quality."

[0004] Although the soft stone board manufactured in the above patent document has advantages such as light weight, its function is single and it is only used as a wall finishing material, and further improvement is still needed. Based on this, the present invention provides a soft stone board with solar photovoltaic and a preparation method thereof to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a soft stone board with solar photovoltaic and a preparation method thereof. The prepared soft stone board with solar photovoltaic not only has good solar light conversion efficiency, but also has excellent flexibility, effectively ensuring its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a soft stone board with solar photovoltaic, wherein the soft stone board is composed of a photovoltaic decorative layer and a base layer bonded by an adhesive;

[0008] The photovoltaic decoration layer includes a first film layer, an amorphous silicon flexible solar thin film battery and a second film layer, wherein the amorphous silicon flexible solar thin film battery is arranged between the first film layer and the second film layer;

[0009] The first film layer is prepared by applying the functional auxiliary material on the surface of the PET film, and then placing it in an oven at 60-70° C. for 14-16 hours;

[0010] The base layer is made of the following raw materials in parts by weight: 20-30 parts of acrylic emulsion, 40-50 parts of Portland cement, 3-5 parts of dibutyl acrylate, 3-5 parts of sodium dodecylbenzene sulfonate, 2-6 parts of potassium sulfamate, 6-10 parts of reinforcing filler and 100-120 parts of water;

[0011] The preparation process of the base layer is as follows:

[0012] Accurately weigh acrylic emulsion, silicate cement, dibutyl acrylate, sodium dodecylbenzene sulfonate, potassium sulfamate, reinforcing filler and water, and mix at 120-140 r / min for 20-30 min;

[0013] The obtained slurry is evenly arranged in a mold and solidified to obtain a base layer.

[0014] The present invention is further configured as follows: the adhesive is a polyurethane sealing adhesive.

[0015] The present invention is further configured as follows: the preparation process of the functional auxiliary material is as follows:

[0016] The composite material is placed in trichlorotrifluoroethane at a solid-liquid ratio of 0.02 to 0.22 g / mL, stirred at 120 to 220 r / min for 20 to 30 minutes, and then potassium persulfate, surfactant and tert-butyl alcohol are added thereto, and the mixing is continued for 10 to 12 minutes;

[0017] Then, the mixture is treated at 94-96°C and 4.1-4.3MPa for 150-200min to obtain a functional auxiliary material;

[0018] Wherein, the addition amount of potassium persulfate is 0.02-0.12% of the mass of the composite material;

[0019] The surfactant is prepared by mixing polysorbate 80 and water at a solid-liquid ratio of 0.11 to 0.31 g / mL, and the amount of the surfactant added is 0.05 to 0.14% of the mass of the composite material;

[0020] The added amount of the tert-butyl alcohol is 0.02-0.08% of the mass of the composite material.

[0021] The present invention is further configured as follows: the composite material is formed by mixing tetrafluoroethylene and ethylene in a mass ratio of 1:0.7-0.9.

[0022] The present invention is further configured such that: the second film layer is a PET film.

[0023] The present invention is further configured as follows: the preparation process of the reinforcing filler is as follows:

[0024] The nanocarbon fibers are placed in a modified solution at a solid-liquid ratio of 0.05 to 0.15 g / mL and ultrasonically treated for 30 to 40 minutes, filtered, and dried at 100 to 120° C. for 12 to 14 hours to obtain pretreated nanocarbon fibers;

[0025] The modified graphene oxide was placed in deionized water and ultrasonically treated for 20 to 30 minutes at a solid-liquid ratio of 0.01 to 0.08 g / mL to obtain a dispersion;

[0026] The pretreated nano-carbon fibers are placed in a dispersion at a mass ratio of 0.1 to 0.2:1, and are heat-treated at 50 to 60° C. for 60 to 80 minutes. After filtration, the pretreated nano-carbon fibers are washed twice with deionized water, and dried at 60 to 70° C. to constant weight to obtain a base material.

[0027] The present invention is further configured as follows: the modified solution is prepared by mixing 3-aminopropyltriethoxysilane and an ethanol aqueous solution with a concentration of 75% in a mass ratio of 0.02 to 0.12:1.

[0028] The present invention is further configured as follows: the preparation process of the modified graphene oxide is as follows:

[0029] The graphene oxide was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.02 to 0.14 g / mL for 20 to 30 minutes, and then a sodium hydroxide aqueous solution with a concentration of 0.4 to 0.6% was added thereto to adjust the pH to 5.1 to 5.6;

[0030] Then, 0.3-0.7% of methyl silicone oil by mass of graphene oxide is added thereto, treated at 120-240 r / min for 20-30 min, then treated at 8000-12000 r / min for 10-16 min, and allowed to stand for 30-40 min, the lower layer of solution is taken out, and dried at 60-70° C. to constant weight to obtain modified graphene oxide.

[0031] The second aspect of the present invention: also provides a method for preparing the above-mentioned soft stone board with solar photovoltaic, comprising the following steps:

[0032] Step 1: Apply adhesive to the surface of the base layer, and then place the photovoltaic decorative layer on the adhesive;

[0033] Step 2: After roller pressing and vacuum treatment by a laminator, a finished soft stone slab with solar photovoltaic properties is obtained.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The soft stone board of the present invention is composed of a photovoltaic decorative layer and a base layer bonded by an adhesive, the photovoltaic decorative layer includes a first film layer, an amorphous silicon flexible solar thin film battery and a second film layer, the amorphous silicon flexible solar thin film battery is arranged between the first film layer and the second film layer, the first film layer is prepared by applying functional auxiliary materials on the surface of a PET film and then placing it in an oven for drying, wherein the base layer is prepared with acrylic emulsion, silicate cement, dibutyl acrylate, sodium dodecylbenzene sulfonate, potassium aminosulfonate, reinforcing filler and water as raw materials. The soft stone board with solar photovoltaic prepared by the present invention not only has good solar light conversion efficiency, but also has excellent flexibility, which effectively guarantees its quality. The soft stone board with solar photovoltaic provided by the present invention and its preparation method have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] This embodiment provides a soft stone board with solar photovoltaic function. The soft stone board is composed of a photovoltaic decorative layer and a base layer bonded by an adhesive.

[0039] Among them, the adhesive is polyurethane sealing adhesive.

[0040] In this embodiment, it should be noted that the polyurethane sealing adhesive was purchased from Hebei Fengsheng Plastic Industry Co., Ltd.

[0041] The photovoltaic decoration layer comprises a first film layer, an amorphous silicon flexible solar thin film battery and a second film layer, wherein the amorphous silicon flexible solar thin film battery is arranged between the first film layer and the second film layer.

[0042] The first film layer is prepared by applying the functional auxiliary material on the surface of the PET film and then drying it in an oven at 60° C. for 14 hours.

[0043] Among them, the preparation process of functional excipients is as follows:

[0044] The composite material was placed in trichlorotrifluoroethane at a solid-liquid ratio of 0.02 g / mL, stirred at 120 r / min for 20 min, and then potassium persulfate, surfactant and tert-butyl alcohol were added thereto, and mixing was continued for 10 min;

[0045] Then, it was treated at 94°C and 4.1MPa for 150min to obtain the functional auxiliary material;

[0046] Wherein, the addition amount of potassium persulfate is 0.02% of the mass of the composite material;

[0047] The surfactant is prepared by mixing polysorbate 80 and water at a solid-liquid ratio of 0.11 g / mL, and the amount of the surfactant added is 0.05% of the mass of the composite material;

[0048] The added amount of tert-butyl alcohol is 0.0% of the mass of the composite material.

[0049] The composite material is made by mixing tetrafluoroethylene and ethylene in a mass ratio of 1:0.7.

[0050] In addition, the base layer is made of the following raw materials in parts by weight: 20 parts of acrylic emulsion, 40 parts of Portland cement, 3 parts of dibutyl acrylate, 3 parts of sodium dodecylbenzene sulfonate, 2 parts of potassium sulfamate, 6 parts of reinforcing filler and 100 parts of water.

[0051] The preparation process of the base layer is as follows:

[0052] Accurately weigh acrylic emulsion, silicate cement, dibutyl acrylate, sodium dodecylbenzene sulfonate, potassium sulfamate, reinforcing filler and water, and mix at 120 r / min for 30 min;

[0053] The obtained slurry is evenly arranged in a mold and solidified to obtain a base layer.

[0054] The preparation process of the reinforcing filler is as follows:

[0055] The nanocarbon fibers were placed in a modified solution at a solid-liquid ratio of 0.05 g / mL and ultrasonically treated for 30 min. After filtration, the solution was dried at 100°C for 12 h to obtain pretreated nanocarbon fibers.

[0056] The modified graphene oxide was ultrasonically treated in deionized water for 20 min at a solid-liquid ratio of 0.01 g / mL to obtain a dispersion;

[0057] The pretreated carbon nanofibers were placed in a dispersion at a mass ratio of 0.1:1, and were heat-treated at 50°C for 60 minutes. After filtration, they were washed twice with deionized water and dried at 60°C to constant weight to obtain a base material.

[0058] Furthermore, the modified solution is prepared by mixing 3-aminopropyltriethoxysilane and an ethanol aqueous solution having a concentration of 75% in a mass ratio of 0.02:1.

[0059] The preparation process of modified graphene oxide is as follows:

[0060] The graphene oxide was placed in deionized water and ultrasonically treated for 20 minutes at a solid-liquid ratio of 0.02 g / mL, and then a 0.4% sodium hydroxide aqueous solution was added thereto to adjust the pH to 5.1;

[0061] Then, 0.3% of methyl silicone oil by weight of graphene oxide was added thereto, treated at 120 r / min for 20 min, then treated at 8000 r / min for 10 min, and allowed to stand for 30 min. The lower layer of solution was taken out and dried at 60° C. to constant weight to obtain modified graphene oxide.

[0062] In this embodiment, it should be noted that nano-carbon fibers were purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., silicate cement was purchased from Hebei McMahon Mineral Products Co., Ltd., acrylic emulsion was purchased from Shandong Junda Chemical Co., Ltd., potassium aminosulfonate was purchased from Shandong Xinghai Chemical Co., Ltd., graphene oxide was purchased from Hubei Darli Chemical Co., Ltd., and methyl silicone oil was purchased from Shandong Yunxin New Materials Technology Co., Ltd.

[0063] Wherein, the second film layer is made of PET film.

[0064] In addition, this embodiment also provides a method for preparing the above-mentioned soft stone board with solar photovoltaic, comprising the following steps:

[0065] Step 1: Apply adhesive to the surface of the base layer, and then place the photovoltaic decorative layer on the adhesive;

[0066] Step 2: After roller pressing and vacuum treatment by a laminator, a finished soft stone slab with solar photovoltaic properties is obtained.

[0067] Example 2

[0068] This embodiment provides a soft stone board with solar photovoltaic function. The soft stone board is composed of a photovoltaic decorative layer and a base layer bonded by an adhesive.

[0069] Among them, the adhesive is polyurethane sealing adhesive.

[0070] In this embodiment, it should be noted that the polyurethane sealing adhesive was purchased from Hebei Fengsheng Plastic Industry Co., Ltd.

[0071] The photovoltaic decoration layer comprises a first film layer, an amorphous silicon flexible solar thin film battery and a second film layer, wherein the amorphous silicon flexible solar thin film battery is arranged between the first film layer and the second film layer.

[0072] The first film layer is prepared by applying the functional auxiliary material on the surface of the PET film and then drying it in an oven at 65° C. for 15 h.

[0073] Among them, the preparation process of functional excipients is as follows:

[0074] The composite material was placed in trichlorotrifluoroethane at a solid-liquid ratio of 0.12 g / mL, stirred at 170 r / min for 25 min, and then potassium persulfate, surfactant and tert-butyl alcohol were added thereto, and mixing was continued for 11 min;

[0075] Then, it was treated at 95°C and 4.2MPa for 175min to obtain a functional auxiliary material;

[0076] Wherein, the addition amount of potassium persulfate is 0.07% of the mass of the composite material;

[0077] The surfactant is prepared by mixing polysorbate 80 and water at a solid-liquid ratio of 0.21 g / mL, and the amount of the surfactant added is 0.09% of the mass of the composite material;

[0078] The added amount of tert-butyl alcohol is 0.02-0.08% of the mass of the composite material.

[0079] The composite material is made by mixing tetrafluoroethylene and ethylene in a mass ratio of 1:0.8.

[0080] In addition, the base layer is made of the following raw materials in parts by weight: 25 parts of acrylic emulsion, 45 parts of silicate cement, 4 parts of dibutyl acrylate, 4 parts of sodium dodecylbenzene sulfonate, 4 parts of potassium sulfamate, 8 parts of reinforcing filler and 110 parts of water.

[0081] The preparation process of the base layer is as follows:

[0082] Accurately weigh acrylic emulsion, silicate cement, dibutyl acrylate, sodium dodecylbenzene sulfonate, potassium sulfamate, reinforcing filler and water, and mix at 130 r / min for 25 min;

[0083] The obtained slurry is evenly arranged in a mold and solidified to obtain a base layer.

[0084] The preparation process of the reinforcing filler is as follows:

[0085] The nanocarbon fibers were placed in a modified solution at a solid-liquid ratio of 0.1 g / mL and ultrasonically treated for 35 min. After filtration, the solution was dried at 110° C. for 13 h to obtain pretreated nanocarbon fibers.

[0086] The modified graphene oxide was ultrasonically treated in deionized water for 25 min at a solid-liquid ratio of 0.04 g / mL to obtain a dispersion;

[0087] The pretreated carbon nanofibers were placed in a dispersion at a mass ratio of 0.2:1, and heat-treated at 55°C for 70 minutes. After filtration, they were washed twice with deionized water and dried at 65°C to constant weight to obtain a base material.

[0088] Furthermore, the modified solution is prepared by mixing 3-aminopropyltriethoxysilane and an ethanol aqueous solution having a concentration of 75% in a mass ratio of 0.07:1.

[0089] The preparation process of modified graphene oxide is as follows:

[0090] The graphene oxide was ultrasonically treated in deionized water at a solid-liquid ratio of 0.07 g / mL for 25 min, and then a 0.5% sodium hydroxide aqueous solution was added thereto to adjust the pH to 5.3;

[0091] Then, 0.5% methyl silicone oil by weight of graphene oxide was added thereto, treated at 180 r / min for 25 min, then treated at 10000 r / min for 13 min, and allowed to stand for 35 min. The lower layer of solution was taken out and dried at 65° C. to constant weight to obtain modified graphene oxide.

[0092] In this embodiment, it should be noted that nano-carbon fibers were purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., silicate cement was purchased from Hebei McMahon Mineral Products Co., Ltd., acrylic emulsion was purchased from Shandong Junda Chemical Co., Ltd., potassium aminosulfonate was purchased from Shandong Xinghai Chemical Co., Ltd., graphene oxide was purchased from Hubei Darli Chemical Co., Ltd., and methyl silicone oil was purchased from Shandong Yunxin New Materials Technology Co., Ltd.

[0093] Wherein, the second film layer is made of PET film.

[0094] In addition, this embodiment also provides a method for preparing the above-mentioned soft stone board with solar photovoltaic, comprising the following steps:

[0095] Step 1: Apply adhesive to the surface of the base layer, and then place the photovoltaic decorative layer on the adhesive;

[0096] Step 2: After roller pressing and vacuum treatment by a laminator, a finished soft stone slab with solar photovoltaic properties is obtained.

[0097] Example 3

[0098] This embodiment provides a soft stone board with solar photovoltaic function. The soft stone board is composed of a photovoltaic decorative layer and a base layer bonded by an adhesive.

[0099] Among them, the adhesive is polyurethane sealing adhesive.

[0100] In this embodiment, it should be noted that the polyurethane sealing adhesive was purchased from Hebei Fengsheng Plastic Industry Co., Ltd.

[0101] The photovoltaic decoration layer comprises a first film layer, an amorphous silicon flexible solar thin film battery and a second film layer, wherein the amorphous silicon flexible solar thin film battery is arranged between the first film layer and the second film layer.

[0102] The first film layer is prepared by applying the functional auxiliary material on the surface of the PET film and then drying it in an oven at 70°C for 16 hours.

[0103] Among them, the preparation process of functional excipients is as follows:

[0104] The composite material was placed in trichlorotrifluoroethane at a solid-liquid ratio of 0.22 g / mL, stirred at 220 r / min for 30 min, and then potassium persulfate, surfactant and tert-butyl alcohol were added thereto, and mixing was continued for 12 min;

[0105] Then, the mixture was treated at 96°C and 4.3 MPa for 200 min to obtain a functional auxiliary material;

[0106] The amount of potassium persulfate added is 0.12% of the mass of the composite material;

[0107] The surfactant is prepared by mixing polysorbate 80 and water at a solid-liquid ratio of 0.31 g / mL, and the amount of the surfactant added is 0.14% of the mass of the composite material;

[0108] The added amount of tert-butyl alcohol is 0.08% of the mass of the composite material.

[0109] The composite material is made by mixing tetrafluoroethylene and ethylene in a mass ratio of 1:0.9.

[0110] In addition, the base layer is made of the following raw materials in parts by weight: 30 parts of acrylic emulsion, 50 parts of Portland cement, 5 parts of dibutyl acrylate, 5 parts of sodium dodecylbenzene sulfonate, 6 parts of potassium sulfamate, 10 parts of reinforcing filler and 120 parts of water.

[0111] The preparation process of the base layer is as follows:

[0112] Accurately weigh acrylic emulsion, silicate cement, dibutyl acrylate, sodium dodecylbenzene sulfonate, potassium sulfamate, reinforcing filler and water, and mix at 140 r / min for 30 min;

[0113] The obtained slurry is evenly arranged in a mold and solidified to obtain a base layer.

[0114] The preparation process of the reinforcing filler is as follows:

[0115] The nanocarbon fibers were placed in a modified solution at a solid-liquid ratio of 0.15 g / mL and ultrasonically treated for 40 min. After filtration, the solution was dried at 120° C. for 14 h to obtain pretreated nanocarbon fibers.

[0116] The modified graphene oxide was ultrasonically treated in deionized water for 30 min at a solid-liquid ratio of 0.08 g / mL to obtain a dispersion;

[0117] The pretreated carbon nanofibers were placed in a dispersion at a mass ratio of 0.1:1, and were heat-treated at 60°C for 80 minutes. After filtration, they were washed twice with deionized water and dried at 70°C to constant weight to obtain a base material.

[0118] Furthermore, the modified solution is prepared by mixing 3-aminopropyltriethoxysilane and an ethanol aqueous solution having a concentration of 75% in a mass ratio of 0.12:1.

[0119] The preparation process of modified graphene oxide is as follows:

[0120] The graphene oxide was placed in deionized water and ultrasonically treated for 30 minutes at a solid-liquid ratio of 0.14 g / mL, and then a 0.6% sodium hydroxide aqueous solution was added thereto to adjust the pH to 5.6;

[0121] Then, 0.7% methyl silicone oil by weight of graphene oxide was added thereto, treated at 240 r / min for 30 min, then treated at 12000 r / min for 16 min, and allowed to stand for 40 min. The lower layer of solution was taken out and dried at 70° C. to constant weight to obtain modified graphene oxide.

[0122] In this embodiment, it should be noted that nano-carbon fibers were purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., silicate cement was purchased from Hebei McMahon Mineral Products Co., Ltd., acrylic emulsion was purchased from Shandong Junda Chemical Co., Ltd., potassium aminosulfonate was purchased from Shandong Xinghai Chemical Co., Ltd., graphene oxide was purchased from Hubei Darli Chemical Co., Ltd., and methyl silicone oil was purchased from Shandong Yunxin New Materials Technology Co., Ltd.

[0123] Wherein, the second film layer is made of PET film.

[0124] In addition, this embodiment also provides a method for preparing the above-mentioned soft stone board with solar photovoltaic, comprising the following steps:

[0125] Step 1: Apply adhesive to the surface of the base layer, and then place the photovoltaic decorative layer on the adhesive;

[0126] Step 2: After roller pressing and vacuum treatment by a laminator, a finished soft stone slab with solar photovoltaic properties is obtained.

[0127] Performance Test:

[0128] The first film layers prepared in Examples 1 to 3 are respectively marked as Examples 1 to 3; and the relevant properties of the first film layers provided by each group are tested as follows:

[0129] Light transmission test: The test method is GB / T 2410-2008, and the test data are recorded in Table 1 below.

[0130] Table 1 Test results of light transmittance performance of each group

[0131] Group Light transmittance (%) Example 1 Group 96.7 Example 2 Group 96.5 Example 3 Group 96.7

[0132] The finished soft stone panels with solar photovoltaic properties prepared in Examples 1 to 3 are marked as Examples 1 to 3 respectively; and the relevant properties of the first film layer provided by each group are tested as follows:

[0133] Flexibility test: The test method is JC / T2219-2014, and the test data are recorded in Table 2 below.

[0134] Table 2 Flexibility test results of each group

[0135] Group Flexibility Example 1 Group No cracks Example 2 Group No cracks Example 3 Group No cracks

[0136] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the soft stone board with solar photovoltaic prepared by the present invention not only has good solar light conversion efficiency, but also has excellent flexibility, which effectively guarantees its quality. This shows that the soft stone board with solar photovoltaic and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0137] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0138] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A soft stone board with solar photovoltaic, characterized in that, The soft stone board is composed of a photovoltaic decorative layer and a base layer bonded by an adhesive; The photovoltaic decoration layer includes a first film layer, an amorphous silicon flexible solar thin film battery and a second film layer, wherein the amorphous silicon flexible solar thin film battery is arranged between the first film layer and the second film layer; The first film layer is prepared by applying the functional auxiliary material on the surface of the PET film, and then placing it in an oven at 60-70° C. for 14-16 hours; The base layer is made of the following raw materials in parts by weight: 20-30 parts of acrylic emulsion, 40-50 parts of Portland cement, 3-5 parts of dibutyl acrylate, 3-5 parts of sodium dodecylbenzene sulfonate, 2-6 parts of potassium sulfamate, 6-10 parts of reinforcing filler and 100-120 parts of water; The preparation process of the base layer is as follows: Accurately weigh acrylic emulsion, silicate cement, dibutyl acrylate, sodium dodecylbenzene sulfonate, potassium sulfamate, reinforcing filler and water, and mix at 120-140 r / min for 20-30 min; The obtained slurry is evenly arranged in a mold and solidified to obtain a base layer.

2. A soft stone board with solar photovoltaic according to claim 1, characterized in that: The adhesive is polyurethane sealing adhesive.

3. The soft stone board with solar photovoltaic according to claim 1, characterized in that: The preparation process of the functional excipient is as follows: The composite material is placed in trichlorotrifluoroethane at a solid-liquid ratio of 0.02 to 0.22 g / mL, stirred at 120 to 220 r / min for 20 to 30 minutes, and then potassium persulfate, surfactant and tert-butyl alcohol are added thereto, and the mixing is continued for 10 to 12 minutes; Then, the mixture is treated at 94-96°C and 4.1-4.3MPa for 150-200min to obtain a functional auxiliary material; Wherein, the addition amount of potassium persulfate is 0.02-0.12% of the mass of the composite material; The surfactant is prepared by mixing polysorbate 80 and water at a solid-liquid ratio of 0.11 to 0.31 g / mL, and the amount of the surfactant added is 0.05 to 0.14% of the mass of the composite material; The added amount of the tert-butyl alcohol is 0.02-0.08% of the mass of the composite material.

4. A soft stone board with solar photovoltaic according to claim 3, characterized in that: The composite material is prepared by mixing tetrafluoroethylene and ethylene in a mass ratio of 1:0.7-0.

9.

5. The soft stone board with solar photovoltaic according to claim 1, characterized in that: The second film layer is made of PET film.

6. The soft stone board with solar photovoltaic according to claim 1, characterized in that: The preparation process of the reinforcing filler is as follows: The nanocarbon fibers are placed in a modified solution at a solid-liquid ratio of 0.05 to 0.15 g / mL and ultrasonically treated for 30 to 40 minutes, filtered, and dried at 100 to 120° C. for 12 to 14 hours to obtain pretreated nanocarbon fibers; The modified graphene oxide was placed in deionized water and ultrasonically treated for 20 to 30 minutes at a solid-liquid ratio of 0.01 to 0.08 g / mL to obtain a dispersion; The pretreated nano-carbon fibers are placed in a dispersion at a mass ratio of 0.1 to 0.2:1, and are heat-treated at 50 to 60° C. for 60 to 80 minutes. After filtration, the pretreated nano-carbon fibers are washed twice with deionized water, and dried at 60 to 70° C. to constant weight to obtain a base material.

7. The soft stone board with solar photovoltaic according to claim 6, characterized in that: The modified solution is prepared by mixing 3-aminopropyltriethoxysilane and an ethanol aqueous solution with a concentration of 75% in a mass ratio of 0.02 to 0.12:

1.

8. The soft stone board with solar photovoltaic according to claim 6, characterized in that: The preparation process of the modified graphene oxide is as follows: The graphene oxide was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.02 to 0.14 g / mL for 20 to 30 minutes, and then a sodium hydroxide aqueous solution with a concentration of 0.4 to 0.6% was added thereto to adjust the pH to 5.1 to 5.6; Then, 0.3-0.7% of methyl silicone oil by mass of graphene oxide is added thereto, treated at 120-240 r / min for 20-30 min, then treated at 8000-12000 r / min for 10-16 min, and allowed to stand for 30-40 min, the lower layer of solution is taken out, and dried at 60-70° C. to constant weight to obtain modified graphene oxide.

9. A method for preparing a soft stone board with solar photovoltaic properties according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Apply adhesive to the surface of the base layer, and then place the photovoltaic decorative layer on the adhesive; Step 2: After roller pressing and vacuum treatment by a laminator, a finished soft stone slab with solar photovoltaic properties is obtained.

Citation Information

Patent Citations

  • Lightweight soft stone plate and preparation method thereof

    CN115196928A